Psychological capital and leadership role under the turbulent conditions in banking sector - Volodymyr Momot; Olena Lytvynenko (Financial Internet Quarterly, 2020)
The article discusses the problems of commercial banks related to the coping with abrupt changes in activities organization due to quarantine and moving to partially remote work. The theoretical considerations concerning psychological capital role at organization operating under the unstable conditions are given and hypothesis regarding psychological capital, its individual components, leadership, leadership styles (types) and the overall effectiveness of the organization are formulated. Empirical evidence which proves formulated hypothesis is presented. Concepts of psychological health and psychological competences are presented. The research conducted shows that the psychological capital of financial institutions employees being monitored during COVID-19 quarantine at Spring 2020 is positively correlated with the impact of transformational leadership on the organization effectiveness.
Keywords: G01; G21; M21; M14; M59; 330; psychological capital; leadership; leadership style; job satisfaction; value system; involvement; effectiveness of the organization; financial organization